Decentralized Control Architecture for Microgrids (International Journal of Innovative Research in Engineering & Management, 2023)
Since its establishment in the late 1800s,  the electrical infrastructure has continued to grow at a  steady rate for the past 100 years. Due to the increasing  dependence on electrical energy, this infrastructure will be  in greater demand. Infrastructures are at their limit, and  equipment must be upgraded on a regular basis. As an  example, if the power lines were adequate for domestic and  commercial loads, but the adoption of electric vehicles  continues to grow, an upgrade might not be feasible. A  better alternative is the micro grid concept, or localized  generation and consumption. However, because the  generation sources are dispersed, controlling them and  coordinating them becomes extremely difficult. Micro grid  architectures with localized control are proposed as a  solution to this problem. Here's a micro grid setup with  separate sources integrated on a common DC bus, as well  as battery storage and power monitoring and protection  systems in-built.
Keywords: PV; micro grid; SPWM; and relay